SMAD4 gene mutation increases the risk of aortic dilation in patients with hereditary haemorrhagic telangiectasia. (15th October 2017) - Vorselaars, V.M.M.; Diederik, A.; Prabhudesai, V.; Velthuis, S.; Vos, J.-A.; Snijder, R.J.; Westermann, C.J.J.; Mulder, B.J.; Ploos van Amstel, J.K.; Mager, J.J.; Faughnan, M.E.; Post, M.C.
Abstract: Background: Mutations in the genes ENG, ACVRL1 and SMAD4 that are part of the transforming growth factor-beta signalling pathway cause hereditary haemorrhagic telangiectasia (HHT). Mutations in non-HHT genes within this same pathway have been found to associate with aortic dilation. Therefore, we investigated the presence of aortic dilation in a large cohort of HHT patients as compared to non-HHT controls. Methods: Chest computed tomography of consecutive HHT patients ( ENG, ACVRL1 and SMAD4 mutation carriers) and non-HHT controls were reviewed. Aortic root dilation was defined as a z-score > 1.96. Ascending and descending aorta dimensions were corrected for age, gender and body surface area. Results: In total 178 subjects (57.3% female, mean age 43.9 ± 14.9 years) were included (32 SMAD4, 47 ENG, 50 ACVRL1 mutation carriers and 49 non-HHT controls). Aortopathy was present in a total of 42 subjects (24% of total). Aortic root dilatation was found in 31% of SMAD4, 2% of ENG, 6% of ACVRL1 mutation carriers, and 4% in non-HHT controls (p < 0.001). The aortic root diameter was 36.3 ± 5.2 mm in SMAD4 versus 32.7 ± 3.9 mm in the non- SMAD4 group (p = 0.001). SMAD4 was an independent predictor for increased aortic root ( β -coefficient 3.5, p < 0.001) and ascending aorta diameter ( β -coefficient 1.6, p = 0.04). Conclusions: SMAD4 gene mutation in HHT patients is independently associated with a higher risk of aortic root and ascending aortic dilation as compared to other HHT patients and non-HHT controls.